Nature's deadliest creatures : visual encyclopedia - Harvey, Derek (New York : DK Publishing, 2018)
Profiles dangerous animals from around the world--including komodo dragons, brown recluse spiders, polar bears, barn owls, and more--and discusses what makes them so deadly.
Includes index.
8.5
3-6
Keywords: Dangerous animals -- Juvenile literature; Poisonous animals -- Juvenile literature; Dangerous animals; Poisonous animals